KERAGAMAN KULTIVAR PURING [Codiaeum variegatum (L.) Rumph. ex. A.Juss] DAN PEMANFAATANNYA DI KAMPUNG TABLANUSU DISTRIK DEPAPRE KABUPATEN JAYAPURA PAPUA - Syan Yubel Kamarea; Konstantina M.B. Kameubun; Maikel Simbiak (NOVAE GUINEA Jurnal Biologi, 2024)
Croton plant [Codiaeum variegatum (L.) Rumph. ex. A.Juss] is an ornamental plant that has many variations, especially variations in shape, color and size of leaves. The identification aims to determine puring cultivars and their use in Tablanusu Village. This research was conducted in Tablanusu village in Depapre District, Jayapura Regency. Data collection techniques in this research used observation, interviews and documentation. The research data was analyzed using qualitative and quantitative analysis. The research results found 35 croton cultivars. Of the 35 cultivars, 31 Croton cultivars have identified trade names, namely brown earring croton, Andreanum croton, gold drill croton, black jack croton, chicken tail croton, bird's eye chili croton, caldium norm croton, cinderella croton, dian sp croton, diane croton, croton dwipa, croton galaxy, croton gold dust, croton holand, croton jet black, croton turtle, croton marcos/plakadot, croton maximum, croton rose, croton miss thailand, croton moon ray, croton nirvana, croton ovalifolium, croton philadelphia, croton picasso painbrush, croton png, red cricle croton, parrot wing croton, mutation egg croton, anchovy croton and cristata swallow croton. The other 4 cultivars have no identified trade names, namely cultivar 1, cultivar 2, cultivar 3, cultivar 4. Croton plants in Tablanusu Village have a relationship between 0.44 and 0.95. People in Tablanusu Village use croton as accessories for traditional ceremonies or traditional dances, as ornamental plants in yards, as plants for fences or area boundaries, and as shade and decoration for graves. Keywords : Diversity, Cultivars, Croton Plants, Tablanusu, Papua